A Correlational Study: The Role of Religiosity and Self-Righteousness in Predicting Aggression among Muslims In Malaysia - Siti Hasanah, Azahari; Nor Asyikin Binti, Sezali (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2021)
Introduction – As the Western media continues to link Islam with terrorism and aggression, many Muslims, especially those who are a minority in their country, struggle with a negative stigma. Purpose – This current research seeks to examine the predictive abilities of religiosity and self-righteousness on aggression among Muslims in Malaysia. Methodology/Approach – An online survey that adapted items from the Religious Commitment Inventory-10 (RCI[1]10), Self-Righteousness Scale (SRS), and Aggression Questionnaire (AQ) were employed. This study hypothesized that aggression is predicted by self[1]righteousness, while religiosity is not predictive of aggression. Participants in this study were recruited through a convenient sampling method whereby the link to access the survey was shared on social media platforms. The participants comprised 66 female respondents while 43 respondents were males; the mode of age for all was 22 years old (N=109). The data collected was analyzed in SPSS using regression analysis to measure the relationship between the variables (religiosity, self-righteousness, and aggression) as well as to examine its predictive capabilities. Findings – The regression analysis model produced R2 = 0.49, F (2, 106) = 2.73, p = .07. Results also showed that RCI-10 was not related to AQ; meanwhile, SRS is predictive of AQ. Hence, the hypotheses of this study were accepted. Originality/ Value/ Implication – These findings imply that perhaps personal interpretation and experiences play a large part in how people interpret their religion and justify aggressive behaviours. Similarly, results indicated that religiosity is not supposed to manifest aggression. This further implies that the way sermons and religious values are being delivered plays a crucial role in fostering aggressive tendencies. It is hoped that the findings herein can be used as a guide for future researchers and aid in reducing negative stigmas on Muslim